Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Belanja Modal pada Kabupaten dan Kota di Provinsi Daerah Istimewa Yogyakarta (DIY) Tahun 2016–2020 - Imam Khulwani; Risal Rinofah; Pristin Prima Sari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to determine the effect of Regional Original Income, General Allocation Funds, Special Allocation Funds, partially and simultaneously effecting Capital Expenditures in Regencies/Cities in the Province of the Special Region of Yogyakarta (DIY) in 2016-2020. The type of research used is the type of quantitative research. Secondary data obtained from the website (http://www.djpk.kemenkeu.go.id). In this study, it was analyzed using descriptive analysis and multiple linear regression analysis and processed with SPSS version 25. The results of this study indicate that partially: the Regional Original Income (PAD) variable has a partial effect on Capital Expenditures in 4 regencies and 1 city in the Special Region of Yogyakarta (DIY), the General Allocation Fund (DAU) does not partially affect Capital Expenditures. , the Special Allocation Fund (DAK) has an effect on Capital Expenditures in 4 districts and 1 city in the Province of the Special Region of Yogyakarta (DIY). Meanwhile, simultaneously: Variables of Local Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) simultaneously have a significant effect on Capital Expenditures in 4 districts and 1 city in the Special Region of Yogyakarta (DIY). ) with the period 2016-2020. Keywords: Regional Original Revenue, General Allocation Fund, Special Allocation Fund, Capital Expenditure.